(3GdSdhc GdGSJgdGcj ddSGFM aj VhA hGbY GdOhd GdeJbOeI hGdOhd GdfGejIs (3OQGSI aj GdCfKQhHhdhLjG GdGbJUGOjIs - (3OYHS(B, (3eMeO jSQj GHQGgjes ((3GdGScfOQjIs (3GdHjWGT SfJQ ddfTQ h GdJhRjYs, 2002)
(3GdeaGgje hGdJUhQGJ hGdGJLGgGJ GdfXQjI Mhd GdSjGMI hGdSGFM hhbJ GdaQGZ hGdESJgdGc(B-(3GdeSdc GdSjGMj(B((3GdSeGJ hGdNUGFU hGdOhGaY hGdMbhb hGdhGLHGJ hGdYhGed GdeNJdaI GdeDKQI(B)-(3GdYhGed GdeNJdaI GdeDKQI aj CfeGW GdGSJgdGc eY GdJWHjb aj GdeLGd GdSjGMj,CfeGW GdSjGMI hCfhGYgG GdeNJdaI heYOdGJ GdGfaGb hGdGSJgdGc(B-(3MeGjI GdeSJgdc GdSjGMjs
Keywords: (3GdSjGMI(B- (3GbJUGOjGJs; (3GdeSJgdchfs